Analisis Konsep dan Implementasi Penilaian Kinerja guru (PKG) dalam Meningkatkan Prestasi Guru MI di Kecamatan Merakurak - Nur Laili Komairatul Fitria; Sutiah, Sutiah (Journal of Education Research, 2024)
Teachers are a key element in the educational process, to become a teacher you must also fulfill several competencies, one of which is teacher performance assessment , which is a performance management assessment system that focuses on teachers which is designed to assess the level of teacher performance in groups and individually. Teacher performance assessment  is a basis or foundation for madrasas and schools for making development decisions in teacher promotion and careers. Assessment that originates from the elements of a teacher's main activities in carrying out their duties for the purpose of professional development, rank and position is defined as an assessment of teacher performance. Teachers need to have four competencies in forming teachers' personalities so that they behave like professional teachers, namely pedagogical, personal, social and professional competencies. The benefit of PKG is to determine the abilities possessed by teachers in carrying out their duties by measuring their mastery of skills and competencies